Victims, nonvictims and their opinions on transitional justice: Findings from the Colombian case (2015)
Victims of armed conflict are often seen as driven by trauma-related stark emotions that differentiate them from nonvictims. Based on this premise, they should hold different views from people who have not been directly affected by war about punishing perpetrators of violence, remembering human rights violations, seeking truth and receiving reparations. The resilience literature, on the contrary, has downplayed the role of traumatic experiences in shaping people's views and rather stressed their ability to cope with adversity. In this article, we ask whether there are any differences in attitudes toward transitional justice mechanisms between victims and nonvictims, using a representative sample of the Colombian population (n1/41,843, of whom 315 are conflict victims). We find almost no statistically significant differences. Psychological resilience among victims may account for this counterintuitive finding. However, we suggest that social desirability biases, a pervasive impact of the long conflict beyond the victim/nonvictim divide and social proximity between victims and perpetrators may also be relevant explanations. Our results are relevant for scholars and policy makers, as they question elements of common (yet untested) wisdom about the political and social impact of violence on individuals' attitudes and about the prospects of peaceful coexistence. © The Authors (2015).